Irradiation-assisted intergranular stress corrosion cracking of austenitic stainless steel in steam-water mixture - Goncharenko, Yu.D.; Kazakov, V.A.; Shamardin, V.K.; Pechyorin, A.M.; Filyakin, G.V.; Ostrovsky, Z.Ye. (Вопросы атомной науки и техники, 2002)
Ціль запропонованої роботи – отримати результати для того, щоб зробити питомий внесок у розуміння механізму
радіаційного обумовленного міжзеренного корозійного розтріскування аустенітних нержавіючих сталей. Цель предложенной работи – получение новых результатов для того, чтобы внести конструктивный вклад в
понимание механизма радиационно-обусловленного межзеренного коррозионного растрескивания аустенитных сталей. The objective is to obtain the new results in order to make a constructive contribution into understanding of the mechanism of
austenitic stainless steels (ASS) irradiation-assisted intergranular stress corrosion cracking (IAISCC).